AN ASSESSMENT ON ACOUSTICAL PROPERTIES OF MEVLEVI LODGES - Firat, Hasan Baran; Can, Zerhan Yuksel (INT INST ACOUSTICS & VIBRATION, 2015)
Comprehensive studies are needed to understand the original acoustical features of the Mevlevi Lodges which are one of the most special examples of the Islamic as well as the Ottoman architecture. Acoustic properties of the whirling halls still need to be studied due to their authentic forms and large volume. A research is being done to reveal the overall acoustic properties of the Mevlevi Lodges. In these assessments, unique identity of Mevlevi Music will also be taken into consideration. Acoustics evaluations of the selected Mevlevi Lodges are aimed to be done after the data held from the in situ acoustical measurements and the Odeon models. Mevlevi Lodges' acoustical properties as well as their differences from the western performance halls will be the results of the research. The preliminary research for the Mevlevi Lodges and the acoustics data of the Galata Mevlevi Lodge will be presented in this paper.
Keywords: Acoustics; Engineering